ANALISIS SEMIOTIKA BARTHES TERHADAP IMPLEMENTASI PEMAKNAAN KATA IBADAH OLEH TAKMIR MASJID PURWOKERTO - Harisman Harisman (Hunafa: Jurnal Studia Islamika, 2023)
The reality of language in human life goes dynamically. That is, there are developments and changes in human language so that it can cause a shift in meaning. Likewise, the meaning of worship at the time of the Apostle has a broader meaning. The author in this case aims to examine the implementation of the meaning of the term worship by the takmir of the mosque in Purwokerto. This research uses a qualitative type of research with data collection using interview, observation and documentation techniques. At the analysis stage, the author uses Barthes semiotics to reveal the implementation of the meaning of worship by the takmir of the Purwokerto mosque. As a result, that the meaning of worship in mosques is implemented only for worship that is mahdhah only. Mosques are not used for other activities as support for mahdhah worship. So the mosque is closed at certain times.